The Appropriate Acquisition Time Interval Following Injection of 99mTc-Sestam ibi with Water Protocol in Single Photon Emission Computed Tomography Myocardial Perfusion Imaging: First Experience in Indonesia - Prasetyo, Nora Anggun; Soeriadi, Erwin Affandi; Budiawan, Hendra; Kartamihardja, Achmad Hussein Sundawa (Medicinus, 2022)
Introduction: According to EANM/ESC guideline, image acquisitions in stress test should be begun at 30-60 minutes after tracer administration. Our center is a referral hospital for nuclear medicine imaging with many patients but limited number of gamma camera. The shorter time between injection of radiopharmaceutical and imaging acquisition will add to the number of examinations that can be performed. The aim of this study was to evaluate the appropriate acquisition time interval with water protocol in 99mTc-Sestamibi SPECT myocardial perfusion imaging.Methods: Patients who were referred to undergo stress MPI between October 2020 to December 2020 were included in this study. Cardiac stress procedure was performed using treadmill with modified Bruce Protocol. Subjects drank a total of 330 mL water following 99mTc-Sestamibi injection. Image acquisitions were performed 10 and 30 minutes afterwards. Quantitative assessment was done by calculating target background ratio (TBR). Statistical analysis was performed using student t-test with Microsoft Excel version 2019. P-value < 0.05 was considered to be statistically significant.Result: Thirty out of 35 subjects were included in this study. Sixteen of them are male and 14 are female with a mean age of 48.7 years old (28 – 80). Mean target background uptake ratio (TBR) in 10- and 30-minutes images were 0.67 (0.44 – 1.11) and 0.76 (0.43 – 1.18) respectively (p-value = 0.15).Conclusion: There was no significant difference of target to background ratio between 10- and 30-minutes acquisition time interval following injection of 99mTc- Sestamibi with water protocol in myocardial perfusion imaging.